1988
DOI: 10.1111/j.1432-1033.1988.tb13992.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural variability of the neutral carbohydrate moiety of cow colostrum κ‐casein as a function of time after parturition

Abstract: New neutral oligosaccharides from cow colostrum rc-casein were identified and characterized by 500-MHz New neutral oligosaccharides from cow colostrum It-caseinoglycopeptide samples (C-terminal part of cow ic-casein, residues 106 -169, containing all the sugars) obtained 15 min, 18 h and 42 h after calving are described. While only one neutral disaccharide GalP(l-+ 3)GalNAc-01 was identified in mature milk Ic-caseinoglycopeptide which had no blood group I specificity, four neutral oligosaccharides (from di-to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Much of the data derived for this concept has come from the dietary profile of children from birth onwards. It has been reported that the glycosylation of milk proteins varies during lactation, this has been shown for the major family of milk glycoproteins, the caseins in both man and cow [ 99 , 100 ] and also for human milk lactoferrin [ 101 , 102 ]. In keeping with this concept, the pattern of low molecular weight oligosaccharides present in mothers-milk is known to change during lactation [ 103 , 104 ].…”
Section: Bacterial Species In the Human Gastrointestinal Tractmentioning
confidence: 99%
“…Much of the data derived for this concept has come from the dietary profile of children from birth onwards. It has been reported that the glycosylation of milk proteins varies during lactation, this has been shown for the major family of milk glycoproteins, the caseins in both man and cow [ 99 , 100 ] and also for human milk lactoferrin [ 101 , 102 ]. In keeping with this concept, the pattern of low molecular weight oligosaccharides present in mothers-milk is known to change during lactation [ 103 , 104 ].…”
Section: Bacterial Species In the Human Gastrointestinal Tractmentioning
confidence: 99%
“…4, 13,14 Recently, a study on proteins of early lactation bovine milk was reported 15 using MALDI-TOF/TOF-MS approaches to monitor changes in time of N-glycan classes (di-, tri-, tetra-antennary chains). The O-glycosylation of bovine milk glycoproteins has been well studied for κ-casein 16 and milk-fat-globule membrane proteins. 17 A more comprehensive overview of all relevant literature known to the authors is presented in Table S1, Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Early studies indicated a higher degree of glycosylation of k-casein in colostrum than in mature milk as well as the presence of an additional sugar moiety, N-acetylglucosamine (GlcNAc) (Guerin et al, 1974;Fournet et al, 1975). As well as the structures already identified above in normal milk, the following structures have been reported: the acidic hexasaccharide, NeuAca (Fiat et al, 1988). As well as the structures already identified above in normal milk, the following structures have been reported: the acidic hexasaccharide, NeuAca (Fiat et al, 1988).…”
Section: Sources Of Heterogeneitymentioning
confidence: 82%
“…The presence of sugars on k-casein was recognized as long ago as 1961 (Alais & Jolles, 1961), and during the 1970s and 1980s, a large number of studies were directed at elucidating the sugar composition, sequence, and sites of attachment to the protein. The major glycan is a tetrasaccharide composed of galactose (Gal), N-acetylgalactosamine (GalNAc), and sialic or neuraminic acid (NeuAc) of the form NeuAca(2-3)Galb(1-3)[NeuAca(2-6)]GalNAc, but monosaccharide (GalNAc), (Fournet et al, 1975;van Halbeek et al, 1980;Fiat et al, 1988;Saito & Itoh, 1992). The relative amounts have been determined by high-performance liquid chromatography (HPLC) as 56.0% tetrasaccharide, 36.9% trisaccharide (18.4% linear and 18.5% branched), 6.3% disaccharide, and 0.8% monosaccharide (Saito & Itoh, 1992).…”
Section: Glycosylationmentioning
confidence: 99%